Current standards for assessing pregnancy status before surgery are subjective and should be replaced with definitive, objective evidence. Issue 2 (May 2018) - Clement, Keiran D; Luhmann, Andreas; Wilson, Michael SJ; Patil, Pradeep
We report a case of a young woman admitted electively for laparoscopic Nissen fundoplication, and again three days post-operatively as an emergency with profuse vomiting and abdominal pain. She underwent diagnostic laparoscopy, and a small gastric perforation was found at the site of the fundoplication and this was suture-repaired. On both admissions, she was "screened" for pregnancy as per current guidelines. On the second admission, following a CT scan, she was found to have a gravid uterus with a foetus of 16–18 weeks' gestation. In the opinion of the authors, this case highlights that current National Institute for Health and Care Excellence guidelines may be insufficient and could lead to unnecessary harm either to mother or foetus pre-, peri- or post-operatively.